Synthesis and Characterization of Lanthanum-Doped Barium-Ferrite/Poly-o-toluidine Composites - Hua, Ren (Asian Journal of Chemistry, 2013)
Electro-magnetic functionalized lanthanum-doped barium-ferrite(BL) particles synthesized by sol-gel selfpropagation high temperature, The final materials of lanthanum-doped barium-ferrite/poly-o-toluidine (BL/POT) composites have been successfully synthesized by in suit chemical polymerization. Crystal structure, morphology and magnetic properties of composites were studied by X-ray diffractometer, Fourier transform infrared spectroscopy, transmission electron microscopy and vibrating sample magnetometer. The results showed that the lanthanum-doped barium-ferrite particles size are 80-100 nm and the lanthanum-doped barium-ferrite/poly-o-toluidine composites size are at the range of 750 nm and when the doped La3+(x = 0.04), there have the best Ms of the BaLaxFe12-xO19/poly-o-toluidine composites.